Penapisan Bakteri Laut Penghasil Antimikroba dari Pesisir Serdang Bedagai Sumatera Utara - Syafrina Sari Lubis (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
Screening of marine bacteria producing antimicrobial was done. Thirty six potential isolates shown antimicrobial activity inhibition zone around colony. Antagonistic assay showed that three isolates SB5, BG3 and BG4 inhibited growth of Staphylococcus aureus, Vibrio sp., Candida albicans with inhibition zone of 31 mm; 27,9mm; 26mm respectively.